COMMUNITY SERVICE EDUCATION ON RISK PERCEPTION AND DECONSTRUCTION OF THE STIGMA OF HIV/AIDS TRANSMISSION IN HIGH-RISK PREGNANT WOMEN AND FAMILIES IN MEDAN TUNTUNGAN DISTRICT - Willhelmina Wahara; Lenny Sepriani Br. Silalahi; Elvyana Saragih (Cattleya Darmaya Fortuna, 2024)
Pregnant women at high risk of HIV/AIDS transmission often face severe psychosocial challenges due to negative stigma from the surrounding environment, which can ultimately hinder access to health services and prevention of mother-to-child transmission (PPIA). This community service activity aims to provide education about risk perception and deconstruct the stigma of HIV/AIDS for high-risk pregnant women and their families in Medan Tuntungan District. The program was implemented on July 16, 2024 through interactive counseling methods, educational dialogues, and counseling sessions to dissect misperceptions related to HIV transmission. The results of the evaluation showed an increase in participants' understanding of the real risk of HIV transmission and a shift in more supportive attitudes in the family environment. This education is expected to reduce stigma, improve compliance with antenatal examinations, and support efforts to effectively prevent HIV transmission in the community.